2021
DOI: 10.4314/ejhs.v31i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of COVID-19 Related Deaths in Ethiopia

Abstract: BACKGROUND: Since the occurrence of COVID-19 in the world, it has claimed nearly 1.39 million human lives in the world and more than 1500 lives in Ethiopia. The number of deaths is increasing with variable distribution in the world. Despite its increasing fatality, the clinical characteristics of the deceased patients are not yet fully known. Analyzing the clinical characteristics of deceased patients will help to improve the outcome of infected patients. Hence, this study aimed to determine the clinical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…On average, 121 new illnesses were recorded each day, that is much lower than the highest daily average ever recorded since the outbreak started. Since the start of the pandemic, there have been 468,345 illnesses and 7,438 deaths attributed to the coronavirus throughout the nation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…On average, 121 new illnesses were recorded each day, that is much lower than the highest daily average ever recorded since the outbreak started. Since the start of the pandemic, there have been 468,345 illnesses and 7,438 deaths attributed to the coronavirus throughout the nation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nine further studies reported descriptive statistics on COVID-19 mortality and hypertension or CVD but did not calculate statistics to formally compare groups. 15,24,26,29,35–39…”
Section: Resultsmentioning
confidence: 99%
“…34 Nine further studies reported descriptive statistics on COVID-19 mortality and hypertension or CVD but did not calculate statistics to formally compare groups. 15,24,26,29,[35][36][37][38][39] Influence of COVID-19 Infection on CVD Two small studies examined the impact of the COVID-19 pandemic on incident CVD and CVD mortality. 30,40 In an observational comparison of stroke admissions before (n=401) and after (n=431) the COVID-19 pandemic in a hospital in Ghana, the stroke admission rate was +7.5% higher in the COVID-19 era (95% CI, 5.1%-10.5%), but the stroke mortality rate was similar (aOR, 1.2 [95% CI, 0.9-1.7]).…”
Section: Covid-19 Mortalitymentioning
confidence: 99%
“…Finally, eleven articles were retrieved and included with a total sample size of 2845 populations. Of these studies, three of them were in China [37][38][39], three in Ethiopia [21,40,41], two in the USA [42,43], One in Pakistan [44], one in South Africa [45], and one in South Sudan [46]. The prevalence of COVID-19-induced ARDS ranges from 9 [40] to 67.3% [39].…”
Section: Study Selection and Characteristics Of The Studiesmentioning
confidence: 99%